2000
DOI: 10.1042/bj3480615
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of haem oxygenase-1 expression and bilirubin production in cellular protection against oxidative stress

Abstract: The inducible isoform of haem oxygenase (HO-1) has been proposed as an effective system to counteract oxidant-induced cell injury. In several circumstances, this cytoprotective effect has been attributed to increased generation of the antioxidant bilirubin during haem degradation by HO-1. However, a direct implication for HO-1-derived bilirubin in protection against oxidative stress remains to be established. In the present study, we examined the dynamics of HO-1 expression and bilirubin production after stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(70 citation statements)
references
References 28 publications
3
67
0
Order By: Relevance
“…The beneficial effect of HO-1 is in general agreement with many prior observations in neural and nonneural systems (Chen et al, 2003;Clark et al, 2000;Turner et al, 1999).…”
Section: Heme Oxygenase As Modulator Of Neural Injurysupporting
confidence: 90%
“…The beneficial effect of HO-1 is in general agreement with many prior observations in neural and nonneural systems (Chen et al, 2003;Clark et al, 2000;Turner et al, 1999).…”
Section: Heme Oxygenase As Modulator Of Neural Injurysupporting
confidence: 90%
“…Together with other genes displaying a similar mRNA profile, these genes may play a role in the pro-apoptotic effect of prolonged culture in G2 and G5 instead of in G10 [12][13][14]26]. Finally, among genes with a V-shaped profile, Mt1a and Hmox1 are considered good markers of beta cell oxidative stress and seem to confer protection against beta cell apoptosis under stressful conditions [29,30]. Other genes with a similar mRNA profile such as Myc and Casp4 may, in contrast, play a role in activation of beta cell apoptosis by oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…The cytoprotective properties of HO-1 have traditionally been attributed to the by-products of heme degradation, namely bilirubin and carbon monoxide (CO). Indeed, within a narrow therapeutic range, these catalytic by-products exert powerful antioxidant [15,31], antiinflammatory [32] and anti-apoptotic effects [33][34][35], leading to reduced infarct size [16,17,[36][37]. However, emerging evidence, suggests that HO-1 may also exert cytoprotective effects, independent of heme breakdown [38] by interacting with survival signaling pathways such as PI3K-Akt and p38.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism by which HO-1 may protect cells or tissues against oxidative injury is by generating bilirubin from catabolism of heme. Several studies have demonstrated that exogenous bilirubin can protect against hypoxia induced injury in cultured cells and in isolated perfused hearts subjected to I/R injury [15][16][17]. Furthermore, a strong correlation has been reported between elevated plasma bilirubin levels and lower risk of cardiovascular diseases [18,19].…”
Section: Introductionmentioning
confidence: 99%